Quality planning and analysis: from product development through use - Juran, J.M.; Gryna, Frank M. (New Delhi: Tata McGraw-Hill, 1993)
Through all editions, Juran's Quality Planning and Analysis has provided students and professionals with an authoritative treatment of the subject that goes beyond statistical techniques. The fifth edition of this highly regarded classic book on managing for quality, Juran's Quality Planning and Analysis for Enterprise Quality, combines the pioneering concepts of Dr. Joseph M. Juran and the teachings of the late Dr. Frank M. Gryna with the insights and experience of today's leading trainers and practitioners at the Juran Institute: Dr. Richard Chua, Executive VP and Joseph A. DeFeo, President & Executive Coach. The trademark Juran Institute approach has been retained, developing the viewpoint that the achievement of quality products and services requires the application of managerial, technological, statistical, and behavioral actions throughout all functions of an organization. With real-world problems provided in each chapter, students are faced with realities that confront managers, designers, engineers, marketers, operations personnel, users, and others involved in enterprise quality. This text will challenge readers to make assumptions, estimate economics, reach data-driven conclusions, and adapt themselves to the imperfect world of the practitioner. Students and professionals will also find this book useful as they prepare for various certifications such as the Certified Quality Engineer, Reliability Engineer, Quality Manager, Six Sigma Green Belt and Black Belt.
Basic concepts -- Companywide assessment of quality -- Quality improvement and cost reduction -- Quality planning and sales income -- Control of quality -- Strategic quality management -- Organization for quality -- Developing a quality culture -- Basic probability concepts -- Statistical tools for analyzing data -- Understanding customer needs -- Designing for quality -- Designing for quality-statistical tools -- Marketing, field performance and customer service -- Marketing, field performance and customer service - statistical tools -- Administrative and support operations -- Quality information systems -- Quality assurance
Includes index
Keywords: Quality Control; Quality Assurance